PENGEMBANGAN FASILITAS PENDIDIKAN UNTUK MEMBENTUK GENERASI UNGGUL DI SMP MUHAMMADIYAH 7 BAYAT KLATEN - Solikin, Mochamad; Fathoni, Rois; Setiawan, Wisnu; Pratiwi, Indah; Aklis, Nur; Umar; Balich, Rama Pratama; Mubarak, Fauzi; Syukur, Muhammad Abdhul; Fatmawati, Denisa Dewi; Alamsyah, Muhammad Nur; Abdullah, Mu’tashim (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
Education is an important sector that creates the nation's next generation, who are superior and competent in their fields. One of the Islamic organizations that is committed to the field of education is Muhammadiyah. This article describes the results of the community service program, which aims to solve the problems of SMP Muhammadiyah 7 Bayat regarding their plans to develop their educational facilities in new locations to enhance students' character. The method of community service begins with a location survey, initial design FGD, initial architectural design, final design FGD, and final architectural design. The results of the service implementation are in the form of final architectural design drawings based on the partners' needs and land area. The shape of the building follows the shape of the triangular land with a vertical facade on the front side of the building to place the school's identity. The school's equipment consists of classrooms, a teacher's office, a principal's office, an administrative room, a library, a basketball field, and other complementary rooms. There is also a two-story mosque above the library building, a BLK room designed on the second floor, and a school hall room on the third floor. Apart from that, the design concept uses a local architectural theme to provide an identity related to the area's potential around the school.